Leadership style in maintenance management / Norhayati Suid - Suid, Norhayati (Faculty of Architecture, Planning and Surveying, 2009)
Objective of this research is to understand about leadership and the implication of leadership in organization. This research also proposes to identify the current leadership in Malaysia and also to identify the acceptable of leadership style to practice in organization. From the research study, I found those majority departments of maintenance management in Malaysia choose the autocratic leadership style that is current practice in Malaysia and also this type of leadership style show the highest result that major of organization can accept this style to practice in their organization.